The Zamboanga standoff : role of the Nur Misuari group - Franco, Joseph (2014)
Gunmen from the Moro National Liberation Front-Misuari Group (MNLF-MG) triggered a hostage crisis in Zamboanga City, Mindanao in the Southern Philippines. The complexity of dealing with an armed secessionist movement that has been able to meld violent and non-violent activities can potentially destabilise the wider region.